Botanical Entanglements : Women, Natural Science, and the Arts in Eighteenth-Century England - Sagal, Anna K., 1985- (Book collections on Project MUSE., 2021)
"This book examines the subversive ways in which women made their mark on the scientific landscape of eighteenth-century England. By taking advantage of intersections between domesticity, femininity, and nature, the writers and artists of this study laid claim to a specific authority on naturalist subjects, ranging from botany to entomology to natural history more broadly"--